Sustainable and Competitive Tourism Concept and Policy Recomendation for Purworejo Torism and Culture Department Case Study (Giyombong-Cepedak-Gunung Condong) as Integrated Tourism Village) - Fauzi, Arief; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2019)
Abstract. Giyombong, Cepedak, and Gunung condong is three tourism destination in Purworejo. Purworejo tourism and culture department has a plan to integrate these three destinations to make it more sustainable. Before preparing large investment, the right and valid integration concept is needed to make the investment right on target. Tourism business is a very volatile, uncertain and influenced by many factors outside of its business context. Investments in that kind of tourism business, especially those are still small and do not have a large marketshare implicate a very high risk. With high risk investors will not be interested participating in the business. The output from this research are guidelines of business integration concept of Giyombong, Cepedak, and Gunung Condong and government policy.Keywords: Integration, Policy, Sustainable, Lean business process..